Notes on a Lesser-known Marian Iconography in 13th and 14th century Ethiopian Painting - Chojnacki, Stanislaw (Aethiopica, 2002)
In this article the early evolution of iconic iconography of the Virgin Mary in Ethiopia is discussed. One particular image is postulated to exist on a painted manbar at Lālibalā. The figure of the Child Mary depicted together with her mother, St. Anne, in the wall painting at the Gannata Māryām Church can also be considered iconic. In the late 14th century and the first decades of the 15th century, three specific groupings of depictions of the Virgin Mary, all clearly having iconic characteristics, have come to light: the Orant Virgin, the seated Hodegetria and the enthroned Virgin holding the Child in her lap. These three forms are characterised by the inclusion of the Archangels Michael and Gabriel, who are shown sheltering her with their outstretched wings. They are depicted holding crosses, while in a particular group of miniatures they extend their hands towards Mary in a gesture of supplication. This Orant form appears to be exceptional, and exists only in 14th century. The Hodegetria type evolved into numerous variants depending on the position of the Child, on Mary's left or right arm. The form of the Enthroned Virgin holding the Child in her lap, faded away in the early 15th century.